(untitled) (Bangladesh Journal of Educational Research, 2026)
This research analyses the syllabi of various English departments in Bangladesh to explore different approaches to poetry in academic studies. This study examines the syllabi of introductory poetry courses in the English departments of four major public universities in Bangladesh to understand how poetry and literature are introduced to first-year students for academic reading and critical appreciation from three perspectives: course design, course objectives, and content selection. The first-year curricula of Bachelor of Arts (BA) programmes across departments have been analysed to understand how introductory poetry courses are placed in the syllabus and how they serve as bridging courses for first-year students. Offering an overview of how poetry and its formal elements are introduced in foundational courses, this exploratory study should help clarify the different visions and missions of English departments in Bangladesh, even though they share the same field of interest. One of the significant findings of this research is that some universities use a similar course design, offering students a dedicated course on critical appreciation before a foundational course on poetry, prose, or drama. Another significant finding of this study is that factors such as poets’ nationalistic identity, race, gender, and academic acceptance play a considerable role in inclusion or exclusion in course content across all these departments. This comparative research on syllabi aims to understand how introductory courses are designed to help students experience pleasure in reading poetry and to contextualise it through a critical, academic lens.